Protein acetylation affects acetate metabolism, motility and acid stress response in Escherichia coli. Issue 11 (28th November 2014) - Castaño‐Cerezo, Sara; Bernal, Vicente; Post, Harm; Fuhrer, Tobias; Cappadona, Salvatore; Sánchez‐Díaz, Nerea C; Sauer, Uwe; Heck, Albert JR; Altelaar, AF Maarten; Cánovas, Manuel
Abstract Although protein acetylation is widely observed, it has been associated with few specific regulatory functions making it poorly understood. To interrogate its functionality, we analyzed the acetylome in Escherichia coli knockout mutants of cobB, the only known sirtuin‐like deacetylase, and patZ, the best‐known protein acetyltransferase. For four growth conditions, more than 2, 000 unique acetylated peptides, belonging to 809 proteins, were identified and differentially quantified. Nearly 65% of these proteins are related to metabolism. The global activity of CobB contributes to the deacetylation of a large number of substrates and has a major impact on physiology. Apart from the regulation of acetyl‐CoA synthetase, we found that CobB‐controlled acetylation of isocitrate lyase contributes to the fine‐tuning of the glyoxylate shunt. Acetylation of the transcription factor RcsB prevents DNA binding, activating flagella biosynthesis and motility, and increases acid stress susceptibility. Surprisingly, deletion of patZ increased acetylation in acetate cultures, which suggests that it regulates the levels of acetylating agents. The results presented offer new insights into functional roles of protein acetylation in metabolic fitness and global cell regulation.